Age Structure of Polygonatum Multiflorum (L.) All. Cenopulations in the Precarpatian Region - Nadiia Riznychuk; Victoria Gniezdilova; Liubov Onyshchenko (Vasyl Stefanyk Precarpathian National University, 2023)
For population studies, the determination of age status is more important than the determination of calendar age. The research conducted in the biotopes of Precarpathian region indicates that according to the age structure the populations of Polygonatum multiflorum (L.) All. belong to the normal type. Self-maintenance of coenopopulations occurs in a combined way as a result of generative and vegetative reproduction, the intensity of which depends on local edaphic and coenotic conditions. The spectra of their age states and reproductive potential are determined by a set of biotope conditions and have species specificity. The nature of the spectrum of age conditions and the value of the recovery index are the most informative indicative markers. Left-sided spectra in combination with high recovery indices indicate the presence of favorable conditions and a high reproduction potential of cenopopulations. The biotopes of felling areas are the most favorable for the realization of the reproduction potential of most cenopopulations of the studied species; the least favorable are the mainline biotopes.